(untitled) (Mustansiria Dental Journal, 2018)
Cephalometric radiographs were taken for (48) subjects with class I occlusion ; (25) females and (23) males , which selected on the standarization of the radiographs. Sample ages range 8-10 years . cephlometric tracing are carried out using the same points, lines, angles and axis of Rickett’s analysis. On comparing the results of this research which is carried out on Iraqi sample with Rickett’s analysis on Caucasian people of the same age appears that there are differences in most of these measurements and this due to racial factors and ethnic variations which play a great role in differences between each ethnic group . The results of Iraqi measurements (mean values ) as fallows:- facial axis (Y-axis) =91.3°; facial depth angle =81.2° ; Frankfort-mandibular plane angle=30°; convexity of point A (mm)=2.7mm; lower incisor to A-pog =1.8mm;angle =26.1° and finally ANS-Xi-Pm angle (lower facial height) = 45.8°.